UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DENGAN METODE CTL SISWA KELAS II SDN TANJUNG PRIOK 01 - Fitriyani, Elsa Adelia; Azzahrah, Aullia; Utami, Nidya Chandra Muji; Dallion, Engga (Dharmas Education Journal (DE_Journal), 2023)
The research have the intention increase beginning reading skills take advantage of the Contextual Teaching and Learning (CTL) method at SDN Tanjung Priok 01. This type is Classroom Action Research (CAR) Kurt Lewin model, with the subject of class II students as many as 32 children (16 boys and 16 girls) located at SDN Tanjung Priok 01 North Jakarta. The data got from observation, tests, and documentation. Then, the data was analyzed by reflecting on the achievement by percentages and strengthened by conclusions. The improvement is proved by the mean value of reading ability in the first cycle which is 85,75 (good), then an increase to 92,50 (very good) in the second cycle. The classical completeness at the initial value was 70% (only 13 students completed) so that cycle I was applied with an increase of 84% (27 students completed). The conclusion from all of the research results is the CTL method can enhance the beginning reading of grade II student of SDN Tanjung Priok 01. Thus, the CTL method be able to use for other research so that learning becomes more varied so that it can improve learning in elementary schools.